PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN PELANGGAN BP BATAM DI MALL PELAYANAN PUBLIK KOTA BATAM - Safitri, Dania Ariska; Hendriati, Yossi (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This research was conducted to determine the effect of service quality and facilities on BP Batam customer satisfaction at Batam City Public Service Mall. The type of research used is by distributing questionnaires. The population in this study are customers who use BP Batam services at the Batam City Public Service Mall. The method used for sampling is a purposive sampling technique, and the samples taken in this study amounted to 100 customers. Based on the results of data processing using multiple linear analysis. The results of the research on the t test show that the service quality variable (X1) has no effect on customer satisfaction (Y) with a tcount (1.881) < ttable (1.984); the facility variable (X2) has an effect on customer satisfaction (Y) with a tcount (3.969) > ttable (1.984), and the service quality and facilities variable has an effect simultaneously with the calculation results Fcount (13.026) > Ftable (3.09), where if Fcount > Ftable. While the R2 value is 0.212 or 21.2% which indicates that the independent variable (X1, X2) affects the dependent variable (Y) by 21.2%.